A study on the socio-economic conditions of migrant workers in rural Thrissur - Divya M V (International Journal of Academic Research and Development, 2018)
Kerala is well-known for the migration of its labour force to different regions, especially to the Gulf countries. The number of Kerala emigrants living abroad today is nearly 2.28 million; another1.15 million people have returned after working abroad. There are, in addition, 3.43 million non-resident Keralites (NRKs) and another 9.31lakh Kerala migrants living in other States in India Kerala became an attractive destination for migrants for them due to the scarcity of labour in the state and high wage compared to other Indian states. Initially they were confined to urban are now they are also working in rural area that too in large numbers. A lot of such migrants came from the neighbouring southern States initially, but workers from West Bengal, Odisha, Bihar, Assam, Uttar Pradesh, Chhattisgarh and Uttarakhand now come to Kerala. They include construction workers, casual labourers, road workers, semi-skilled carpenters, masons, plumbers, electricians, and, of late, farmworkers, domestic helps and hotel employees. Their living conditions are very poor.